2021
DOI: 10.31219/osf.io/njr5u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A survey of researchers' needs and priorities for data sharing

Abstract: PLOS has long supported Open Science. One of the ways in which we do so is via our stringent data availability policy established in 2014. Despite this policy, and more data sharing policies being introduced by other organizations, best practices for data sharing are adopted by a minority of researchers in their publications. Problems with effective research data sharing persist and these problems have been quantified by previous research as a lack of time, resources, incentives, and/or skills to share data. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Despite high levels of data reuse, researchers in most disciplines except Physical Sciences usually struggle to find datasets to reuse. Hrynaszkiewicz et al (2021) reported similar findings for their overall study population. The study results also support the findings of Kratz and Strasser (2015) that most researchers read relevant papers to find reusable datasets, with web searches and disciplinary repository searches also being common.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Despite high levels of data reuse, researchers in most disciplines except Physical Sciences usually struggle to find datasets to reuse. Hrynaszkiewicz et al (2021) reported similar findings for their overall study population. The study results also support the findings of Kratz and Strasser (2015) that most researchers read relevant papers to find reusable datasets, with web searches and disciplinary repository searches also being common.…”
supporting
confidence: 76%
“…Their study did not report disciplinary differences, however. In a recent survey (using multiple online recruitment methods), 52% of 728 respondents self-reported reusing others' research data, but difficulties in finding appropriate data were common (Hrynaszkiewicz et al, 2021). Since finding data is critical to reusability, it is important to understand disciplinary differences in the core issues.…”
Section: Introductionmentioning
confidence: 99%
“…Both the survey questions used and the resulting anonymised data are available from figshare at https://doi.org/10.6084/m9.figshare.13858763 (Harney et al 2021).…”
Section: Data Accessibility Statementmentioning
confidence: 99%
“…The anonymized survey data and survey instrument will be made available on Figshare at https://doi.org/10.6084/m9.figshare.22522372 (Hrynaszkiewicz, Harney & Novich, 2023).…”
Section: Open Science Practicesmentioning
confidence: 99%